Study on the Spatial and Temporal Differences of Water Poverty in the Yellow River Basin and Its Influencing Factors - WANG Shuhe (Renmin Zhujiang)
In order to scientifically and reasonably evaluate the current situation of water poverty in the Yellow River Basin,and strengthen the planning and management of the sustainability of water resources in the Yellow River Basin,this paper builds a water poverty index model based on the theory of water poverty,measures the level of water poverty of 9 provinces in the Yellow River Basin from 2011 to 2017 by the model,and analyzes its temporal and spatial differences and influencing factors.The results show that:①The water poverty of the 9 provinces in the Yellow River Basin was serious overall,the water poverty gap was widening year by year,and the WPI rankings of the provinces were changed.②There were significant spatial differences in the level of water poverty,including severe water poverty,moderate water poverty,and mild water poverty.③From the overall perspective of the Yellow River Basin,the industrial structure had a negative impact,while the environmental regulation,technical level,farmland water conservancy facilities construction and soil erosion control area had positive impacts;from a provincial perspective,the key factors affecting the level of water poverty in each province were different,based on which suggestions on promoting the efficient use of water resources and alleviating the water poverty are put forward.